1980
DOI: 10.1177/001112878002600303
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Legal Representation of the Economically Disadvantaged: Beyond Assembly Line Justice

Abstract: In Houston, Texas, court-appointed attorneys represent indigent criminal defendants. Are defendants with court-appointed attorneys more likely to receive a punitive disposition (conviction versus nonconviction; a prison sentence rather than probation or a fine) than defendants represented by private, retained counsel? Five hundred and eighty-six defendants were selected at the time of charge and followed for one year or until their cases were disposed. When charge and previous convictions were controlled, cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Their analysis of conviction rates revealed no advantage for either type of attorney. Wheeler and Wheeler (1980) and Taylor, Stanley, DeFlorio, and Seekamp (1973) similarly found no effect for attorney type in their study of defendants in Houston and San Diego. Nardulli (1986) found that attorney type had no effect regarding securing plea bargains.…”
Section: Empirical Research On Attorney Type and Case Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…Their analysis of conviction rates revealed no advantage for either type of attorney. Wheeler and Wheeler (1980) and Taylor, Stanley, DeFlorio, and Seekamp (1973) similarly found no effect for attorney type in their study of defendants in Houston and San Diego. Nardulli (1986) found that attorney type had no effect regarding securing plea bargains.…”
Section: Empirical Research On Attorney Type and Case Outcomesmentioning
confidence: 89%
“…For example, Skolnick (1967) suggested that defendants represented by public defenders will get better plea bargains because prosecutors are more willing to share information with public defenders than with privately retained attorneys. Other researchers agree with this assessment citing studies that reveal criminal defendants represented by public defenders do not fare worse than those represented by private attorneys (Casper, 1972;Levin, 1977;McIntyre, 1987;Oaks & Lehman, 1970;Silverstein, 1965;Wheeler & Wheeler, 1980). These researchers suggest that critics "have tended to underestimate the quality of defense provided by the public defender" (Skolnick, 1967, p. 67).…”
Section: Public Defenders Versus Private Attorneysmentioning
confidence: 98%
“…Research regarding the effects of type of legal representation (e.g., private attorney versus public defender) has been mixed, with some studies finding little or no significant effect of type of representation on sentence severity (Wheeler and Wheeler 1980; Clarke and Kurtz 1983; Willison 1984), and others reporting better outcomes for defendants with privately retained attorneys (Holmes et al. 1996).…”
Section: Empirical Research On Sentencing Outcomesmentioning
confidence: 99%
“…A large group of studies found that criminal defendants represented by public attorneys did not fare worse than did those represented by private attorneys (Casper, 1978;Levin, 1977;McIntyre, 1987;Oaks & Lehman, 1970;Silverstein, 1965;Wheeler & Wheeler, 1980). Skolnick (1967) argued that critics tended to underestimate the quality of defense provided by public defenders.…”
Section: Public Defense Under Research Scrutinymentioning
confidence: 99%